Strategies in Real Time: Unconscious Strategy Use in Consecutive Interpreting - Olabinjo, Yewande M. (NIU Journal of Humanities, 2026)
This article investigates the largely unconscious use of interpretative strategies in consecutive interpreting within high level diplomatic settings, drawing on the author’s experience as a language consultant in the Nigeria–China strategic partnership. Grounded in equivalence-based translation theory and the Interpretive Theory of Translation, it conceptualizes consecutive interpreting as a real time, sense-oriented process comprising comprehension, de verbalization, and reformulation, in which interpreters rely on cognitive representations rather than surface linguistic forms. Adopting Li’s (2015) taxonomy of knowledge, language, meaning and delivery-based strategies, the study identifies how anticipation, paraphrasing, compression, omission, text expansion, and other techniques are mobilised, often implicitly, to manage cognitive load and communicative goals alongside core note taking principles of economy, instantaneous seizability, and individuality. The discussion further examines practical challenges—time management, abbreviations, uniformity of reaction, professional jargon, numbering systems, and shifts between professional and casual registers—and illustrates how these factors affect message fidelity and rapport in diplomatic encounters. The article argues that while many strategies emerge from deep seated linguistic competence and situational awareness rather than explicit training, systematically foregrounding strategy awareness and sense-oriented processing in interpreter education can enhance accuracy, cultural sensitivity, and communicative effectiveness in complex cross-cultural negotiations. Keywords: Interpretation, Consecutive Interpretation, Strategies, Time Management;